2014
DOI: 10.3109/10715762.2014.991725
|View full text |Cite
|
Sign up to set email alerts
|

Ankyrin is the major oxidised protein in erythrocyte membranes from end-stage renal disease patients on chronic haemodialysis and oxidation is decreased by dialysis and vitamin C supplementation

Abstract: Chronically haemodialysed end-stage renal disease patients are at high risk of morbidity arising from complications of dialysis, the underlying pathology that has led to renal disease and the complex pathology of chronic kidney disease. Anaemia is commonplace and its origins are multifactorial, involving reduced renal erythropoietin production, accumulation of uremic toxins and an increase in erythrocyte fragility.Oxidative damage is a common risk factor in renal disease and its co-morbidities, and is known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
5
1
Order By: Relevance
“…peroxiredoxin‐2), protein aggregation/complexation (e.g. spectrin–Hb complex , fragmentation, oxidation /carbonylation (e.g. ankyrin ) and activation (e.g.…”
Section: Rbcs In Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…peroxiredoxin‐2), protein aggregation/complexation (e.g. spectrin–Hb complex , fragmentation, oxidation /carbonylation (e.g. ankyrin ) and activation (e.g.…”
Section: Rbcs In Esrdmentioning
confidence: 99%
“…spectrin–Hb complex , fragmentation, oxidation /carbonylation (e.g. ankyrin ) and activation (e.g. of calpain following increase in cytosolic calcium) (Table ).…”
Section: Rbcs In Esrdmentioning
confidence: 99%
“…Yang et al [4] found limited evidence to suggest that nandrolone decanoate can increase plasma TP (MD 0.40 g/L, 95% CI 0.13 to 0.67), levels compared with Epo. Ruskovska et al [5] found TP carbonyls reduced by vitamin C supplementation (2 × 500 mg vitamin C per day for 4 weeks) either under or not Epo dialysis in end-stage renal disease patients than control ones. The present authors found the Ischemia for 45 min followed by reperfusion for 60 min (group A); 2) Ischemia for 45 min followed by reperfusion for 120 min (group B); 3) Ischemia for 45 min followed by immediate Epo intravenous (IV) administration and reperfusion for 60 min (group C); 4) ischemia for 45 min followed by immediate Epo IV administration and reperfusion for 120 min (group D).…”
Section: Introductionmentioning
confidence: 98%
“…For example, ROS are involved in cell signaling, cell division, and protection against infections and carcinogenesis (MITTAL et al, 2014;SIES, 2017;PATTERSON et al, 2019). However, high levels of reactive species leading to oxidative distress are associated with lipid peroxidation, protein oxidation and DNA damage (RUSKOVSKA and BERNLOHR, 2013;NIKITAKI et al, 2015;RUSKOVSKA et al, 2015). On the other side, cellular antioxidant defense comprises enzymes that include superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, thioredoxins and others, and non-enzymatic antioxidants such as glutathione, carotenoids and the antioxidant vitaminsvitamin E and C (TRABER and STEVENS, 2011).…”
Section: Introductionmentioning
confidence: 99%